Preparing the inevitable: how JUNBI eases the burden of death planning - Mohamad Handal, Syairunessa Farhana; Mohamad Yussuf, NurFakiera; Nurdin, Nur’ Atasha Amiera; Karia, Muhammad Firdaus; Aziz, Adrianna (Universiti Teknologi MARA, Kedah, 2023)
Prioritizing and preparing for needs are rather difficult when someone we love passes away. When it comes to managing funeral preparation, it can be overwhelming because we are dealing with stress and sadness at the same time. Therefore, it is crucial that we sort everything out though we are overwhelmed in shock over the loss. JUNBI, which means "preparation" in Japanese, an application is designed to assist users to make funeral less overwhelming and more manageable. It features a checklist of important documents to obtain, an arrangement of death certificates, a platform to store their will and other legal documents, and a tool to help users to plan funerals. This application also has a function that enables users to for search funeral packages or specific business that handles funeral service arrangements. JUNBI provides users with a list of funeral homes and packages in their area, as well as consumer reviews and ratings. Users simply enter the deceased's name, date of death, religion, and address, and it will display a directory of the cemetery area and funeral directors, along with the pricing information. Once those decisions are made, the application connects the bereaved to an operator who finalizes the preparations and provides all the requisite paperwork that one needs after death. Users can also use the application to book appointments with funeral homes. The features are accessible for both Muslim and non-Muslim users. Prayer recitation in the Quran or the Bible, Qibla direction, and prayer time with several sorts of settings, as well as funeral tutorial video, are among the many beneficial features of the application, and it is a full program for Muslim and Non- Muslim users’ fundamental daily activities guidance.